UPAYA PENINGKATAN PENGETAHUAN PELAPISAN LOGAM DI SMK ASTRINDO - Mukhammad Khumaidi Usman; Amin Nur Akhmadi (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
Components and accessories for motor vehicles, accessories for personal items, furniture accessories, folding chairs, various office equipment, agricultural equipment, household accessories, and various industrial equipment are finished by electroplating. It aims to have a good appearance, for example associated with a good, shiny and brilliant appearance that can provide satisfaction to the owner with the aesthetic value that is applied. The city of Tegal is the Java Sea. This makes the main commodity, namely fisheries and most of the people always active in the sea, the use of a product or object made from metal in this area is very vulnerable to corrosive hazards due to the relatively high salt content in coastal areas, this is what can reduce the aesthetic value of a product and if the use of metal materials can not be handled properly it will be quickly affected by corrosion attacks, so it is necessary to have a solution to be able to improve the situation by using supporting equipment such as electroplating. The purpose of this PKM activity is to provide knowledge of metal plating, provide training in the coating process with the electroplating crom method, provide training and understanding of the use of personal protective equipment and hazards when practicing metal coatings. PKM activities were carried out on January 14 and 15, 2020 by providing materials and practices for electroplating and the use of personal protective equipment in the workplace. Results of community service There is an increase in vocational students' knowledge about metal coatings, students are able to practice metal coatings with the electroplating crom method and are able to practice the use of self-protection tools